Lysyl Oxidase Expression Is Decreased in the Developing Diaphragm and Lungs of Nitrofen-Induced Congenital Diaphragmatic Hernia - Takahashi, Toshiaki; Friedmacher, Florian; Takahashi, Hiromizu; Daniel Hofmann, Alejandro; Puri, Prem (European Journal of Pediatric Surgery, 2015)
Introduction Malformation of the nonmuscular tissue components in congenital diaphragmatic hernia (CDH) is thought to underlie the diaphragmatic defect, causing intrathoracic herniation of abdominal viscera and thus disturbing normal lung development. It has been shown that diaphragmatic and pulmonary morphogeneses require the structural integrity of connective tissue, and developmental mutations that inhibit the formation of extracellular matrix (ECM) result in CDH with hypoplastic lungs. Lysyl oxidase (lox), an extracellular enzyme that catalyzes the cross-linking of ECM proteins, plays an essential role during diaphragmatic and pulmonary development by controlling the formation of connective tissue. Furthermore, lox−/− knockouts exhibit abnormal connective tissue with diaphragmatic defects and impaired airway morphogenesis. We designed this study to investigate the hypothesis that diaphragmatic and pulmonary lox expression is decreased in the nitrofen-induced CDH model.Materials and Methods Timed-pregnant Sprague-Dawley rats were exposed to either nitrofen or vehicle on gestational day 9 (D9), and fetuses were harvested on selected time points D15 and D18. The micro-dissected fetal diaphragms (n = 48) and lungs (n = 48) were divided into two groups: control and nitrofen-exposed samples (n = 12 per specimen and time point, respectively). Diaphragmatic and pulmonary gene expression levels of lox were analyzed by quantitative real-time polymerase chain reaction. Immunohistochemical staining was performed to evaluate lox protein expression in diaphragms and lungs.Results Relative mRNA expression of lox was significantly reduced in diaphragms and lungs of nitrofen-exposed fetuses on D15 (0.29 ± 0.08 vs. 0.12 ± 0.05; p < 0.05 and 0.52 ± 0.44 vs. 0.20 ± 0.04; p < 0.05) and D18 (0.90 ± 0.25 vs. 0.57 ± 0.23; p < 0.05 and 0.59 ± 0.26 vs. 0.35 ± 0.09; p < 0.05) compared with controls. Diaphragmatic and pulmonary immunoreactivity of lox was markedly decreased in nitrofen-exposed fetuses on D15 and D18 compared with controls.Conclusions Decreased lox expression during diaphragmatic development and lung branching morphogenesis may interfere with normal cross-linking of ECM proteins, disrupting the integrity of connective tissue, and contributing to the diaphragmatic defect and impaired airway formation in the nitrofen-induced CDH model.
Keywords: lysyl oxidase; diaphragm; lung; nitrofen; congenital diaphragmatic hernia